Nano-structured Cellulose as Green Adsorbents for Water Purification: A Mini Review - Ibrahim, H.; Sazali, N.; Ibrahim, I. N.; Sharip, M. S. (Journal of Applied Membrane Science & Technology, 2019)
Celluloses are natural polysaccharides that have garnered attentions in recent years due to their sustainability, availability and notable applications in various fields. Whilst demand of clean water sources keep increasing, modified nano-structured cellulose derived from agricultural waste showed a good prospect in adsorbing pollutants from water. To date, large number of studies have reported the performance of nanocellulose in removing wide range of pollutants from effluents. The purpose of this mini review is to present an overview of existing literatures on the utilization of nanocellulose-based materials as adsorbent for water remediation and make aware of possible development of integrating adsorption and nanotechnology for water separation and purification.